The Construction of Web Navigation Model in Online Automated Universities' Students Matching System (OAUSMS) - Shamsul Jamel Elias; Jamaluddin Jasmis; Rohaizak Omar; Mohd Rizaimy Shaharudin; Suhardi Wan Mansor (2010)
Navigational contexts are defined and access structures are added in this stage as a finalized form of web navigation model. As a result, this research is targeted to eliminate user frustration as a cause of lost in hyperspace. Online Automated Universities' Students Matching System (OAUSMS) is an existing web-based system that focused on the implementation of data warehousing as the main features of system's development. The development of this system was more to technology oriented without conducting any formal navigational approach. The navigation model is built in two stages. The first one develops a model of rough navigation structure based on navigational classes and links which is called navigational class model. The second one refines this model on describing how objects can be grouped to optimize navigation and collaborate to fulfill the navigation. (Authors' abstract)